Karcagi honvédek Észak-Erdély és Kárpátalja védelmében a II. világháború idején - Pintér Zoltán Árpád (II. Rákóczi Ferenc Kárpátaljai Magyar Főiskola-"RIK-U" Kft., 2017)
Karcag városa és népessége 1944 őszén a német–szovjet haderők összecsapásának területévé vált. Mind a lakosság, mind a város súlyos károkat szenvedett, azonban ezzel korántsem ért véget a település II. világháborús veszteséglajstroma. A városból a II. világháborús részvétel folyamán túlnyomó többségében két alakulathoz soroztak be honvédeket. E karcagi katonák története, mozgósítása és frontharcai azonban kevéssé ismertek. Tanulmányom e katonáknak kíván emléket állítani.

Резюме. Місто Корцог стало восени 1944 року ареною запеклих боїв між німецькими і радянськими військами. Місто сильно постраждало, а його населення зазнало величезних втрат. Але цим список втрат, яких зазнав населений пункт під час Другої світової війни, зовсім не вичерпався. Під час Другої світової війни переважна більшість чоловічого населення міста служила у двох військових частинах. Дуже мало відомо про їх історію, мобілізацію і участь у боях на передовій. Мета нашого дослідження полягає в тому, щоб пам’ять про цих солдатів залишилась живою.

Abstract. The city of Karcag and its population in fall of 1944 became the clash scene of German-Soviet forces. Both the people and the town suffered severe damage, but this is far from the full losses which the settlement suffered in the war. The Hungarian Army mobilized the local men from the city in two batallions during the war. The history of these soldiers and troops, their mobilization and frontline struggles, however, are little known. This paper intends to commemorate those soldiers.
Солдати з Корцога на захисті Північної Трансильванії та Закарпаття під час Другої світової війни
Armed Forces of Karcag in the Protection of Northern Transylvania and Transcarpathia during World War II
https://kmf.uz.ua/wp-content/uploads/2017/12/Acta2017_szines.pdf
https://opac3.brff.monguz.hu:443/hu/record/-/record/bibBRF00005708
Keywords: II. világháború; magyar gyalogsági alakulatok; Karcag; harcok Kárpátalján